Record 5.3 Gbit/s Transmission over 50m 1mm Core Diameter Graded-Index Plastic Optical Fiber - Visani, D.; Okonkwo, C.; Loquai, S.; Yang, H.; Shi, Y.; Van Den Boom, Henrie; Diteweig, A. M. H.; Tartarini, G.; Schmauß, Bernhard; Randel, S.; Koonen, A. M. J.; Tangdiongga, E. (OSA Optics and Photonics Congress, Advanced Photonics, BGPP Topical Meeting, Karlsruhe, 21.-24. Juni, 2010)
We report multi-Gbit/s capacity in 1-mm diameter graded index plastic optical fiber exploiting low-cost eye safe compliant transceivers. Transmission rates between 5.3 and 7.6 Gbit/s are achieved for lengths between 10 and 50 m using DM
lhft_intern.bib::Visani10